SELECTING PEDAGOGICAL GEOTOPES IN URBAN ENVIRONMENT - Φέρμελη Γ.; Μαρκοπούλου-Διακαντώνη Α. (Bulletin of the Geological Society of Greece, 2018)
Landscape is our modern environment and the rocks that constituting are simultaneous the materials from which are made our cities. May be, some students have seen these geological outcrops, but what are they knowing about the way that they have formed, the way that they act on humans and the way that humans act on them? It is very important the selection of urban pedagogical geotopes because their study will contribute in the understanding of the local geological history, and they will help each student separately to develop useful skills and also they will sensitize the general public. There are three cities types or three sections in the cities that they can coexist in a city or it can appear one or a combination of two (Tab. 1). In type 1, exist impressive or simply obvious natural geological resources. In type 2, the appearance of geological natural resources is very limited, but exists. In these two types of cities, we are looking for "typical geotopes" and there is the opportunity to promote the geological natural resource in the urban environment and indicate his relation with historical, social and cultural development of city. In type 3, does not exist the least appearance of geological resources. In this category belong usually the centres of big cities and the probability to find typical geotopes is minimal. In this type, if we want to promote the idea of geological heritage we should "create" a geological resource that means a "non typical geotope". In these cases the built environment - buildings, statues, monuments (Tab. 5), even cemeteries, streets mainly pedestrian zones Tab. 6), pavements and other constructions which their materials (Tab. 7) (rocks and constructions materials) are emanating from geological natural resources – can constitute a "not typical geotope". Educationally these "non typical geotopes" offer a great challenge to discover the local geological history. As a "non typical geotope" in Athens is proposed the "appearance" of Iridanos river in the METRO Station Monastiraki (Tab. 8).